Organic acids metabolism and GABA shunt involved in maintaining quality of Malus domestica by methyl jasmonate treatment. (October 2022) - Fan, Yiting; Li, Canying; Zhu, Jie; Sun, Lei; Huang, Rui; Guo, Mi; Wu, Yushuo; Ge, Yonghong
Graphical abstract: Highlights: MeJA maintained higher flesh firmness, SSC, succinic and tartaric acids contents in apples. MeJA reduced respiratory intensity and ethylene release in apples. MeJA enhanced the the activities and gene expressions of NAD-MDH, NAD-IDH and Mit-ACO. MeJA down-regulated GAD, GABA-T, NADP-ME, PEPC, CS and Cyt-ACO activities and gene expressions. Abstract: Apples (cv. Golden Delicious) were used as the materials to investigate methyl jasmonate (MeJA) dipping on quality parameters, organic acids metabolism and GABA shunt during storage at 21 ± 1 °C and 75 ± 5 % relative humidity. Results demonstrated that MeJA treatment reduced mass loss, respiratory intensity and ethylene release, and maintained higher flesh firmness and soluble solid content of apples. MeJA also decreased malic acid content, increased succinic and tartaric acids contents, and inhibited cytoplasmic aconitase (Cyt-ACO), NADP-malate (NADP-ME), phosphoenolpyruvate dehydrogenase (PEPC), mitochondrial citrate synthase (Mit-CS), glutamate dehydrogenase (GAD), and GABA transferase (GABA-T) activities in apples. NADP-isocitrate dehydrogenase (NADP-IDH), mitochondrial cis -aconitase (Mit-ACO), and cytoplasmic NAD-malate dehydrogenase (CytNAD-MDH) activities in apples were also enhanced by MeJA dipping. Moreover, MeJA dipping enhanced MdCytNAD-MDH and MdNADP-IDH expressions, and down-regulated MdGAD, MdGABA-T, MdNADP-ME, MdPEPC, MdCyt-ACO and MdMit-CS expressions in apples. These results suggest that MeJA dipping can maintain storage quality of "Golden Delicious" apples by regulating organic acids metabolism and GABA shunt.